Blocking the Charge Recombination with Diiodide Radicals by TiO2 Compact Layer in Dye-Sensitized Solar Cells. Issue 9 (1st January 2019) - Nonomura, Kazuteru; Vlachopoulos, Nick; Unger, Eva; Häggman, Leif; Hagfeldt, Anders; Boschloo, Gerrit
Abstract : The addition of a compact titanium dioxide (TiO2 ) layer between the fluorine-doped tin oxide (FTO) coated glass substrate and the mesoporous TiO2 layer in the dye-sensitized solar cell (DSC) based on the iodide/triiodide redox couple (I − /I3 − ) is known to improve its current-voltage characteristics. The compact layer decreases the recombination of electrons extracted through the FTO layer with I3 − around the maximum power point. Furthermore, the short-circuit photocurrent was improved, which previously has been attributed to the improved light transmittance and/or better contact between TiO2 and FTO. Here, we demonstrate that the compact TiO2 layer has another beneficial effect: it blocks the reaction between charge carriers in the FTO and photogenerated diiodide radical species (I2 − ). Using photomodulated voltammetry, it is demonstrated that the cathodic photocurrent found at bare FTO electrodes is blocked by the addition of a compact TiO2 layer, while the anodic photocurrent due to reaction with I2 − is maintained.